Doença ortopédica do desenvolvimento em equinos - Santos, Larissa Tavares dos (Universidade Estadual Paulista (Unesp), 2022)
The objective of this review is to present information impartially and objectively about developmental orthopedic disease in horses. Developmental Orthopedic Disease (DOD) is a term used to refer to musculoskeletal disorders that occur during the growing period of the horse. The common factor is endochondral ossification disorder. With multifactorial causes, genetic selection, rapid growth, nutritional disbalance in the developmental stages, high intake of energy, precocity in physical exercise, among other aspects generally linked to iatrogenesis, stand out. Flexor, angular and rotational deformities, osteochondritis dissecans, and physeal chondrodysplasia are the diseases related to DOD that should be highlighted in studies that seek, in addition to treatments for their correction, also seek to prevent these occurrences

Esta revisão tem por objetivo, apresentar informações de maneira imparcial e objetiva a respeito da doença ortopédica do desenvolvimento em equinos. Doença Ortopédica do Desenvolvimento (DOD) é um termo utilizado para se referir a afecções musculoesqueléticas que ocorrem durante o período de crescimento dos equinos. O fator comum é o distúrbio da ossificação endocondral. Com causa multifatorial, destaca-se a seleção genética, crescimento rápido, desequilíbrio nutricional nas fases de desenvolvimento, excesso energético alimentar, precocidade nos exercícios físicos, entre outros aspectos geralmente vinculados à iatrogenia. As deformidades flexoras e angulares e rotacionais, a osteocondrite dissecans, a condrodisplasia fiseal são as enfermidades relacionadas à DOD que devem ser destacadas nos estudos a busca de tratamentos para correção destas assim como a prevenção das mesmas
Developmental orthopedic disease (DOD) in horses
Keywords: Osteocondrite dissecans.; Condrodisplasia fiseal;; Deformidades angulares;; Deformidades flexoras;; Doença ortopédica do desenvolvimento;